Bereavement during the COVID-19 Pandemic: Impact on Coping Strategies and Mental Health. Issue 4 (2nd October 2022) - Fisher, Joscelyn E.; Rice, Alexander J.; Zuleta, Rafael F.; Cozza, Stephen J.
Abstract : The COVID-19 coronavirus has caused 5.4 million deaths worldwide, including over 800, 000 deaths in the United States (as of December 2021). In addition to these staggering statistics, an even greater number of individuals have died from other causes during the COVID-19 pandemic. As a result, a large portion of the global population has faced bereavement during the COVID-19 pandemic and resulting quarantine. The often rapid and unexpected nature of COVID-19 deaths and the presence of pandemic-related stressors and living restrictions make it more difficult for individuals bereaved during the pandemic to implement effective strategies for coping with the loss compared to non-pandemic periods. Quarantine-related constraints (e.g., social distancing, availability of and access to resources) impede coping strategies that have been found to be adaptive after a loss, such as supportive (e.g., seeking emotional and instrumental support) and active (e.g., problem-focused and cognitive reframing) coping, and they augment avoidant strategies (e.g., substance use, denial, and isolation) that have been found to be maladaptive. Poorer mental health outcomes (including prolonged grief disorder; PGD) have been associated with less healthy coping. This article reviews research findings regarding bereavement during the COVID-19 pandemic, discusses the effects of pandemic-related stressors on bereavement coping strategies, and proposes how different types of coping during the pandemic may account for the poorer mental health outcomes described in recent reports. Interventions for promoting adaptive coping strategies and minimizing maladaptive coping strategies are also outlined.